Construction and application of digital creative platform for digital creative industry based on smart city concept. (October 2020) - Yong, Xiang; Xinxin, Tian; Su, Zhou; Yao, Wei; Rui, Chen
Highlights: Give play to the advantages of information and communication. Analyzes the conceptual connotation of smart city and smart city system. Integrated broadcast systems play an important role in the development of urban intelligence. Abstract: Smart cities use the resources of the new generation of information technology and broadband networks to leverage the advantages of information and communication to build a smart environment for urban development, provide efficient and flexible support for urban management and operations, and provide more humane and more convenient services to the public. The ability to manage and control is a necessary condition for realizing a smart city. This paper uses video streaming media forwarding technology to create a digital creative industry based on the concept of smart city to encourage the public to actively participate in it, effectively promote the promotion and dissemination of cultural heritage. Based on the design goals, architecture, user groups and licensing operations, this paper expounds the idea of constructing cultural heritage management based on the concept of smart city. On this basis, the application selection and effect of the platform are evaluated initially, and the prospect is put forward. Graphical abstract: With the continuous development of digital multimedia technology in intelligent, wireless and high-definition technology, platform "intellectualization" is the next area to be improved. Image, graphical abstract